2014
DOI: 10.2147/mder.s63918
|View full text |Cite
|
Sign up to set email alerts
|

Usability of devices for self-injection: results of a formative study on a new disposable pen injector

Abstract: This article presents a late-stage formative usability study of a pen-injector platform device. Such devices are used for the subcutaneous delivery of biopharmaceuticals, primarily for self-administration by the patient. The study was conducted with a broad user population, defined to represent user characteristics across a range of indications. The goals of the study were to confirm that the pen could be used without recurring patterns of use errors leading to hazardous situations, to evaluate the comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 15 publications
(12 reference statements)
1
24
0
3
Order By: Relevance
“…With regard to the "disposal" category, one must draw a distinction between the complete disposal of the device and (for devices that can be used to administer multiple doses) disposal of the needle only. One publication stated that the inner needle cap was used for disposal instead of the outer needle cap (Lange et al, 2014). In another case, the needle was not safely disposed of (Schertz et al, 2011).…”
Section: Categories Of Identified Use Errors and Close Callsmentioning
confidence: 99%
See 3 more Smart Citations
“…With regard to the "disposal" category, one must draw a distinction between the complete disposal of the device and (for devices that can be used to administer multiple doses) disposal of the needle only. One publication stated that the inner needle cap was used for disposal instead of the outer needle cap (Lange et al, 2014). In another case, the needle was not safely disposed of (Schertz et al, 2011).…”
Section: Categories Of Identified Use Errors and Close Callsmentioning
confidence: 99%
“…Errors related to an "incorrect dose setting" were most common. These refer to either setting up an incorrect dose (Stauder et al, 2014;Fujioka et al, 2015;Rohrer et al, 2013;Jeannerot et al, 2016;Lange et al, 2014;Schertz et al, 2011;Pfützner et al, 2012;Mahony et al, 2015;Saunders et al, 2012) or not setting a dose at all (Fujioka et al, 2015;Rohrer et al, 2013). A close call was also reported in Table 1 Categories of use errors and close calls (Continued)…”
Section: Categories Of Identified Use Errors and Close Callsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the study indicated that training should be spaced over two sessions by a physician. Another study was conducted on the usability of a self-injector [2]. Participants were given the self-injector and an IFU, then asked to inject into a pad.…”
Section: Introductionmentioning
confidence: 99%